2015
DOI: 10.1186/s13550-015-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Early side effects and first results of radioligand therapy with 177Lu-DKFZ-617 PSMA of castrate-resistant metastatic prostate cancer: a two-centre study

Abstract: BackgroundRadioligand therapy (RLT) with 177Lu-DKFZ-617 PSMA (Lu-PSMA) (prostate-specific membrane antigen) is a novel targeted therapy of metastatic prostate cancer. We analysed retrospectively the early side effects and the response rate in the first patients, who received a therapy with Lu-PSMA in our departments.MethodsRLT was performed in ten hormone- and/or chemo-refractory patients with distant metastases and progressive disease (mean age 73.5 years). 68Ga-PSMA HBED-CC PET/CT was performed in all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
207
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(223 citation statements)
references
References 23 publications
5
207
1
10
Order By: Relevance
“…Standard administered activity of 177 Lu PSMA has been variable across the currently published literature as institutions undertake safety and toxicity trials 3, 5, 7, 8, 20, 21, 24, 25, 26, 27, 28, 29. Injected doses have ranged from 3 to 8 GBq per single injections with up to six injections given to men, generally at a minimum 6‐weekly intervals.…”
Section: Practical Aspects Of Lu‐177 Psma Administrationmentioning
confidence: 99%
“…Standard administered activity of 177 Lu PSMA has been variable across the currently published literature as institutions undertake safety and toxicity trials 3, 5, 7, 8, 20, 21, 24, 25, 26, 27, 28, 29. Injected doses have ranged from 3 to 8 GBq per single injections with up to six injections given to men, generally at a minimum 6‐weekly intervals.…”
Section: Practical Aspects Of Lu‐177 Psma Administrationmentioning
confidence: 99%
“…Simultaneously, the PSA response rates are lower in comparison to the older 131 I-PSMA-RLT data exploiting the full 1 Gy red-marrow tolerance limit (10,16). Surprisingly, none of the authors (22)(23)(24)(25)(26)(27)(28) discussed the possibility that escalation of 177 Lu treatment activity to an estimated redmarrow absorbed dose between 0.2-1.0 Gy should still be well tolerable but offers the chance to further improve anti-tumor-activity because a positive dose/responserelationship is normally expected in radiotherapy. Therefore, after clinical introduction of 177 Lu-PSMA-617, for us it seemed ethical mandatory to increase treatment activity until either non-dramatically grade-1/2 toxicities appear or patients achieve enduring remissions.…”
Section: Responsementioning
confidence: 99%
“…Since 2015, several studies reported promising results for response rates and a favorable safety profile after radioligand therapy (RLT) with 177 Lu-PSMA-617 in patients with metastatic castration-resistant prostate cancer (mCRPC) (12)(13)(14)(15)(16). In a single-center study of 28 patients, a slight improvement of survival compared with a matched group of best supportive-care patients (historical population) was demonstrated (16).…”
mentioning
confidence: 99%